Structure elucidation of female-specific volatiles released by the parasitoid wasp Trichogramma turkestanica (Hymenoptera: Trichogrammatidae) - Tröger, Armin; van Beek, Teris A.; Huigens, Martinus E.; Silva, Isabel M. M. S.; Posthumus, Maarten A.; Francke, Wittko (Beilstein Journal of Organic Chemistry, 2014)
Females of the parasitoid wasp Trichogramma turkestanica produce the putative polydeoxypropionates (2E,4E,6S,8S,10S)-4,6,8,10-tetramethyltrideca-2,4-diene and (2E,4E,6S,8S,10S)-4,6,8,10-tetramethyltrideca-2,4-dien-1-ol or their enantiomers as sex specific volatiles. The structures were assigned on the basis of GC–MS investigations using synthetic reference compounds.
Keywords: natural products; structure elucidation; sex specific; Trichogramma turkestanica; volatile deoxypropionates